Comparison of combined hormonal vaginal ring with ultralow-dose combined oral contraceptive pills in the management of heavy menstrual bleeding: A pilot study. (2nd January 2016) - Agarwal, N.; Gupta, M.; Kriplani, A.; Bhatla, N.; Singh, N.
Abstract : The aim of this study was to compare combined hormonal vaginal ring with ultralow-dose combined oral contraceptive (COC) pills in management of heavy menstrual bleeding (HMB). Fifty patients were randomised into Group I: vaginal ring ( n = 25) and group II: COC pills ( n = 25). Menstrual blood loss (MBL) was assessed at baseline, 1, 3 and 6 months (while on treatment) and at 9 months (3 months after stopping therapy). There was significant reduction in baseline pictorial blood loss assessment chart (PBAC) score from 440 ± 188 (Mean ± SD) to 178 ± 95, 139 ± 117, 112 ± 84 and 120 ± 108 in group I and from 452 ± 206 to 204 ± 152, 179 ± 125, 176 ± 164 and 202 ± 167 in group II at 1, 3, 6 and 9 months, respectively ( p = 0.001). Reduction in MBL was 72% and 62% at 6 months and up to 71% and 55% at 9 months in group I and group II, respectively ( p = 0.001). Reduction in MBL with ring was greater at higher baseline PBAC score but lesser in patients with fibroid > 2 cm. Combined vaginal hormonal treatment for HMB is as effective as oral hormonal therapy, with minor and transient side effects and persistence of response after cessation of therapy.